Challenges of creative collaboration in geographical research. (April 2020) - Boyd, Candice P; Barry, Kaya
There is a long history of collaboration between artists and geographers, with creative forms of research and dissemination of findings taking shape as artworks. In addition, there has been significant push from academia for researchers to maximise their research in ways that cater to, and engage with, broader public audiences. Art and creative practices tap into this through formats such as exhibitions, performances and participatory workshops which draw upon arts-based research methodologies with which geographers are becoming increasingly engaged. However, with this enthusiasm to adopt art practices for research dissemination purposes, tensions can arise in determining the levels of collaboration and authorship between artists and geographers, especially when the artist is employed as a research assistant on the project. In this 'In Practice' article, we explore the tensions and challenges that creative collaborations produce with respect to copyright and authorship, specialist skills and the delicate balance of doing creative research as part of a research team. We argue that geographers and artists need to address these issues from the outset and revisit them throughout the research process, and we offer some suggestions for how art–geography research collaborations might best be negotiated.